ACTUALIZATION OF ALI YAFIE'S ECOLOGICAL FIQH IN THE DYNAMICS OF INDONESIAN MUSLIM THOUGHT - Ahmad Lailatus Sibyan; Muhammad Wafi Abdillah (UIN Kiai Haji Achmad Siddiq Jember, 2023)
Ecological damage is a real threat to human survival. Ecological imbalance is the leading cause of various natural disasters. Human superiority and anthropocentrism views on science, technology, and religious legitimacy are the arguments for exploiting nature. Religious regulations in the form of laws on nature conservation are urgently needed to overcome these problems. One of them is actualizing and contextualizing fiqh on environmental sustainability. Therefore, this research explores Ali Yafie's thoughts on interpreting the science of fiqh in ecological sustainability. The study uses a descriptive analysis method to analyze Yafie's ideas on the dynamics of environmental fiqh actualization in Indonesia. This article elaborates on five primary components of life (al-daruriyyat or al-kulliyat al-khams) that all humankind must adequately maintain. The five components are hifz al-nafs (protection of life), hifz al-'aql (maintaining the mind), hifz al-mal (protection of property), hifz al-nasl (maintaining posterity), and hifz al-din (maintaining religion). Yafie added that one crucial principle in the five components is hifz al-bi'ah (preserving the environment). This results from his ijtihad in preserving ecology, namely the balance of the relationship between humans and their surroundings. Yafie concluded that the law of protecting and preserving the environment is mandatory (fard al-kifayah) that will be accounted for in this life and the afterlife.